Assembly line balancing improvement : a case study in an electronic industry - Siti Farahin, Badrul Hisham (2013)
Line balancing is about arranging a production line so that there is an even flow of production from one work station to the next. Line balancing also a successful tool to reduce bottleneck by balancing the task time of each work station so that there is no delays and nobody is overburden with their task. This thesis presents a case study on a line balancing problem in an electronic company and the study focused on assembly line 11 and 12 which produced inductor model HA00-08464 LFTR. This study aims to improve the productivity and line efficiency also to recommend improvement activities based on the line balancing and analysis done in the simulation model. The simulation was done by using Tecnomatix Plant Simulation. All the data needed for the line balancing analysis was collected and a line balancing model equipped with manual calculation was done. This data gathered is then simulated in Tecnomatix Plant Simulation. Among the improvement activities conducted in order to balance the line was combining a few process into one, transformation from manual process to mechanization, and removing waste from the line. Throughout the study, three layouts were proposed. Among these three layouts only one will be proposed to the company. The layout proposed has a better line efficiency and rate of productivity.